CARS FOR INTERIOR DESIGN WEBSITE DESIGN SEAT "USARITA" USING MACROMEDIA DREAMWEAVER 8.0 - Ahmad Yuleindra Pratama; Linda Wahyu Widianti, SKom., MMSI (Jurnal Sistem Informasi, 2008)
In the development of rapid information technology today, so getting it easy for everyperson in getting information. Information can be obtained in various ways,especially for car seats modification. Therefore efforts Jok Mobil Service Station"USARITA" offers products such as materials and car seats are also offered online toordering products.